2019
DOI: 10.1103/physreva.99.023837
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit interactions and chiroptical effects engaging orbital angular momentum of twisted light in chiral and achiral media

Abstract: There is recurrent interest in the orbital angular momentum (OAM) conveyed by optical vortices, which are structured beams with a helically twisted wavefront. Particular significance is attached to the issue of how, in its interactions with matter, light conveying OAM might prove sensitive to the relative handedness and degree of twist in the associated optical wavefront. As a result of recent experimental and theoretical studies, the supposition that beams with OAM might enable discrimination between opposite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 84 publications
1
38
0
Order By: Relevance
“…Very recently, the QED theory was experimentally vindicated in the observation of modified selection rules for absorption of OAM light in which two units of angular momentum, 2 , were transferred to the valence electron of a 40 Ca + ion through an E2 transition-one quantum of angular momentum from the spin angular momentum, and one from the OAM [221]. Alongside this recent accomplishment, there has also been a proof, again via QED, that the optical OAM of twisted light can produce chiroptical phenomena dependent on the direction of an optical vortex twist in both chiral and achiral matter [37,38,[222][223][224][225]. With these successes-some illustrated in Fig.…”
Section: B Original Predictions Of Qedmentioning
confidence: 99%
“…Very recently, the QED theory was experimentally vindicated in the observation of modified selection rules for absorption of OAM light in which two units of angular momentum, 2 , were transferred to the valence electron of a 40 Ca + ion through an E2 transition-one quantum of angular momentum from the spin angular momentum, and one from the OAM [221]. Alongside this recent accomplishment, there has also been a proof, again via QED, that the optical OAM of twisted light can produce chiroptical phenomena dependent on the direction of an optical vortex twist in both chiral and achiral matter [37,38,[222][223][224][225]. With these successes-some illustrated in Fig.…”
Section: B Original Predictions Of Qedmentioning
confidence: 99%
“…Recently, it has shown that the weak optical quadrupole interaction in atoms can be improved considerably while the atom interacts at near resonance with an optical vortex [12,17]. In addition, the LG mode is investigated in the case of the quadrupole approximation and with an appropriate choice of the winding number l of the vortex, the process involving the dipole-forbidden, but quadrupole-allowed, transitions in atoms can be realized [12].…”
Section: Laguerre Gaussian Modesmentioning
confidence: 99%
“…Then, some appropriate theoretical examinations that are concerned with the exploration of the quadrupole interaction effects have been suggested [10][11][12]. Some such studies are concerned with the exploration of the effects of magnetic-dipole interaction, in the context of the magnetic mirrors applications [13][14][15], while others are dealt with the electric-quadrupole aspects in the framework of the atoms motion in a laser field [7][8][9][10][11][12] and other studies are concerned with the chiroptical interactions using vortex light, which can only occur through the quadrupole transitions [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the interaction involves quadrupole couplings, to calculate the matrix element requires determination of the gradient of the electric field. This has previously been calculated for Laguerre-Gaussian modes 38 and is given as follows:…”
Section: Scattering Theorymentioning
confidence: 99%